2011
DOI: 10.1590/s1984-82502011000300005
|View full text |Cite
|
Sign up to set email alerts
|

The Liquisolid technique: an overview

Abstract: A novel "Powder Solution Technology" involves absorption and adsorption efficiency which makes use of liquid medications, drug suspensions admixed with suitable carriers, coating materials and formulated into free flowing, dry looking, non adherent and compressible powder forms. Based upon a new mathematical model expression, improved flow characteristics and hardness of the formulation has been achieved by changing the proportion of Avicel ® PH 200 and Aerosil ® PH 200 from 50:1 ratio to 5:1 and in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 17 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…As for the dissolution rate, it was reported that dissolution rate was affected by the excipients ratio (R). More specifically, dissolution rate could be increased proportionally as excipients ratio R was increased until an apparent maximum plateau was reached at R value greater than 20 37 , thus three excipients ratios (10, 15 and 20) were selected to analyze the effect of excipients ratio R on the dissolution rate. Avicel PH 102 is one of the most commonly used carriers.…”
Section: Solubility Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As for the dissolution rate, it was reported that dissolution rate was affected by the excipients ratio (R). More specifically, dissolution rate could be increased proportionally as excipients ratio R was increased until an apparent maximum plateau was reached at R value greater than 20 37 , thus three excipients ratios (10, 15 and 20) were selected to analyze the effect of excipients ratio R on the dissolution rate. Avicel PH 102 is one of the most commonly used carriers.…”
Section: Solubility Studymentioning
confidence: 99%
“…However, only small amount of dissolution fluid was involved in the formation of the stagnant diffusion layer around the drug particle. Consequently, at such a micro-environment of diffusion layer, the infinite amounts of liquid vehicle may act as a cosolvent, leading to the enhancement of saturated solubility (C S ) of tadalafil 37 . An increase in C S would undoubtedly increase the drug concentration gradient (C S À C), and thus improved the dissolution rate according to the Noyes-Whitney equation 54 .…”
Section: In Vitro Dissolution Studymentioning
confidence: 99%
“…The method employed for tableting in this study was direct compression for which the drug should possess good flow properties in order to get a uniform feed as well as reproducible filling of tablet dies, the failing of which may lead to high dose variations. In order to ensure the flow properties of the liquisolid systems for direct compression into tablets, angle of repose measurements, Carr's index and Hausner's ratios were adopted for further evaluation [27][28][29][30] . Pure drug lornoxicam exhibited high angle of repose value (45.07 ± 0.73) indicating extremely poor flow property.…”
Section: Micromeritic Propertiesmentioning
confidence: 99%
“…Generally, the solid liquid compacts with high R-value comprised of the relatively large amount of powder admixture (carrier and coating materials) and the amount of non-volatile solvent available per powder substrate is relatively larger. Hence the solid liquid compacts with high R values showed a better dissolution profile [29,30].…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 99%